2020
DOI: 10.1101/2020.09.01.278606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response to Kozlovet al.: Inaccurate estimation of biases in herbarium specimen data

Abstract: SummaryKozlov and colleagues1 call into question the application of herbarium specimens to quantify historical patterns of herbivory2–5. It is already widely appreciated that collectors of herbarium specimens may tend to avoid insect damage, thus making herbivory estimates from herbarium specimens potentially down-biased2. However, Kozlov et al. additionally suggest that variation in sampling selectivity among collectors may misrepresent patterns of herbivory in nature. The authors sought to quantify these bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These differences varied between species, which suggests that assuming lower levels of herbivory across all herbarium specimens is not valid when using herbarium data (Kozlov et al, 2020). However, a recent re-analysis of the data collected by Kozlov et al (2020) showed that with sufficient samples (more than 10 data points), herbivory levels of field-observed samples and herbarium specimens are highly correlated, and that there is little difference in sampling bias across species (Meineke et al, 2020). For our study, we therefore assume that if a collection bias exists, it would be consistent for native and non-native species and would therefore not affect the interpretation of our results.…”
Section: Sample Yearmentioning
confidence: 99%
“…These differences varied between species, which suggests that assuming lower levels of herbivory across all herbarium specimens is not valid when using herbarium data (Kozlov et al, 2020). However, a recent re-analysis of the data collected by Kozlov et al (2020) showed that with sufficient samples (more than 10 data points), herbivory levels of field-observed samples and herbarium specimens are highly correlated, and that there is little difference in sampling bias across species (Meineke et al, 2020). For our study, we therefore assume that if a collection bias exists, it would be consistent for native and non-native species and would therefore not affect the interpretation of our results.…”
Section: Sample Yearmentioning
confidence: 99%
“…1). Despite the tendency of botanists to collect attractive specimens (and those potentially free of pests; Kozlov et al ., 2020), recent evidence indicates that these collecting biases are not strong enough to offset the generation of meaningful conclusions (Meineke et al ., 2020b).…”
Section: Historical Baselines Provided By Herbaria and Their Use In Tmentioning
confidence: 99%
“…In another example, Kozlov et al [36] compared herbivory estimates from herbarium specimens and randomized samples and found that collectors may manifest biases in herbivory captured on herbarium specimens by collecting leaves that are minimally damaged. However, this study also represents a cautionary example of why robust sample sizes are needed to develop baseline datasets [37] and underscores the need for statistical tools that assess the sample sizes needed to achieve accurate estimates, such as power analyses and rarefaction curves.…”
Section: Trait Biasmentioning
confidence: 99%